The concept of Metamorphosis in the teaching of drawing. Stimulus for creativity and sustainability in experiences in the 10th and 12th Grades in compulsory education in Portugal (Revista Apotheke, 2024)
This article stems from research conducted within the scope of the Master’s Degree in Visual Arts Teaching, focusing on supervised teaching practice at Henriques Nogueira Secondary School (Torres Vedras, Portugal). The study involved a 10th-grade class in Drawing A and a 12th-grade class in Art Workshop. The main objective was to investigate the influence of two Didactic Units centered on the theme of Metamorphosis on the development of creativity, considering the teaching-learning process of Drawing in two different school years. Thus, the study sought to answer the central question: ‘Can the concept of Metamorphosis be adopted as a framework to develop and stimulate students’ creativity in Drawing projects?’ The results demonstrate that the concept of Metamorphosis, being a metaphor for continuous transformation, can serve as a facilitating framework for creativity in Drawing, facilitating processes of formal variation and improvisation. This work contributes to understanding the importance of Metamorphosis as an enriching concept in Drawing teaching, promoting students’ creative development.
Keywords: metamorphosis; creativity in drawing; teaching visual arts